Drastic enhancement on Fenton oxidation of organic contaminants by accelerating Fe(iii)/Fe(ii) cycle with l-cysteine. Issue 53 (16th May 2016) - Luo, Lianshun; Yao, Yuyuan; Gong, Fei; Huang, Zhenfu; Lu, Wangyang; Chen, Wenxing; Zhang, Li
Abstract : The introduction ofl -cysteine to the Fenton system improved the oxidation efficiency dramatically by accelerating the transformation from Fe(iii ) to Fe(ii ) and significantly promoted the generation of ˙OH. Abstract : The development of a highly efficient and pH-tolerant Fenton system has been one of the most important and challenging goals in water remediation. Herein, a green natural organic ligand, l -cysteine (Cys), was innovatively introduced into Fenton's reagent to construct an excellent catalytic oxidation system. The introduction of Cys into the Fenton system expanded the effective pH range up to 6.5 and achieved a superior oxidation efficiency, representing about 70% higher removal ratio and 12 times higher reaction rate constant with methylene blue dye as the probe compound. The Cys-driven Fenton reaction presented an outstanding pH adaptability and oxidative activity compared with other common organic ligands or reducing agent-modified Fenton reactions. An investigation of the reaction mechanism indicated that the addition of Cys into the system accelerated the Fe(iii )/Fe(ii ) cycle, and led to a relatively steady Fe(ii ) recovery, which enhances the generation of hydroxyl radicals (˙OH). The presence of Cys in the Fenton system remarkably reduced the apparent activation energy from 95.90 to 47.93 kJ mol −1 . The findings from this study provide a feasible approach for a highly efficient and pH-tolerant wastewater treatment process with environmentally benign characteristics, and initiates an inspiring research domain of amino acids in the environmental catalysis field.